The Role Of Sociology Teachers In Fostering Social Attitudes In The Sociology Learning Process For Class X IPS At Pontianak Islamic High School - Yeni, Yeni; Bahari, Yohanes; Okianna, Okianna (Universitas Tanjungpura, 2024)
The sociology teacher carries out his a role model, motivator and guide in developing the social attitudes of class X IPS students. The role of the sociology teacher is as a guide in developing the social attitudes of class X IPS students with several strategies, good examples of discipline and self-confidence. The role of teacher as a motivator in developing the social attitudes of class The role of the teacher as a guide in developing the social attitudes of class. The roles of the teacehr as a role model, motivator, and guide in developing students